All in the (Definition of) Family: Transnational Parent–Child Relationships, Rights to Family Life, and Canadian Immigration Law. (March 2023) - Redmond, Melissa; Martin, Beth
International human rights conventions, Canadian law and academic research all support the right to family life. Internationally and domestically, multiple definitions of family are recognized, acknowledging that long-term interpersonal commitments can be based on biological relationships as well as co-residential, legal, and emotional ties. Yet, the Canadian immigration system's limited and exclusionary understanding of parent–child relationships complicates migrant family reunification. Drawing on qualitative interview and survey data from separated families and key informants who support them, we analyze national status and class assumptions embedded in Canadian immigration standards. We argue that Canadian immigration policies disproportionately deny the right to family life to transnational Canadians and their children who hail from the Global South and/or who are socio-economically disadvantaged. Immigration policies neither recognize the globally accepted "best interests of the child" welfare standard nor the human right to family life. We offer suggestions for addressing these inequities in practice and policy.